The Potential of Coffee and Cocoa Shell Waste as An Energy Source: Analysis of Characteristics of Briquettes From Coffee and Cocoa Shell Waste Through The Carbonization Process - Kresna Mulya Santosa; Hendy Firmanto; Ilham Mufandi; Novia Anggraeni (Agroindustrial Technology Journal, 2023)
This research aims to compare the characteristics of briquettes as an energy source produced from coffee shell waste and cocoa waste. The briquette-making process involves carbonization to produce charcoal as the primary raw material for briquettes. Carbonization time varies, influenced by the type of waste and size of the material. After that, the charcoal is reduced and sifted into fine and coarse powder. Briquette molding uses pressure using a pipe as a mold. The characteristics of briquettes are analyzed through water content, density, burning rate, and ash content. The research results show differences in characteristics between coffee and cocoa waste. The carbonization process affects the time and mass difference of raw materials. Cocoa pod shells require the longest (Â±35 minutes), while cocoa bean shells require the shortest (Â±17 minutes). Next, making briquettes involves molding and pressing using a pipe as a mold. The results showed that waste cocoa pod shells and cocoa bean shells produced more briquettes than waste coffee pod shells and coffee bean shells. The moisture content of briquettes from all types of waste meets the standards, but the density of the raw material for coffee husk waste is low, while the briquettes have a high density. The burning rate of briquettes varies, with cocoa bean shell briquettes having the fastest burning rate and producing much smoke. The ash content of cocoa pod husk briquettes exceeds the standard, while cocoa bean husk briquettes have low ash content. The density of the raw material is correlated with the moisture content of the briquettes. The highest burning rate occurs in cocoa bean shell briquettes, influenced by low density and high water content. The ash content of the briquettes meets standards, except for cocoa shell briquettes. This research proves that cocoa and coffee shell waste can be processed into briquettes with different characteristics.